Fast and low cost biosynthesis of AgNPs with almond leaves: medical applications with biocompatible structures: Fast and low cost biosynthesis of AgNPs - Aktepe, Necmettin; Baran, Ayşe (Progress in Nutrition, 2021)
In this study, silver nanoparticles (AgNPs) were obtained in a low cost, easy and simple way by using the leaf extract of Prunus dulcis L. (almond tree) growing in the Mardin region. Characterization of AgNPs obtained by biosynthesis: Fourier Transform Infrared Spectroscopy (FTIR), X-Ray Diffractometer (XRD), UV-visible spectrophotometer (UV-Vis.), Scanning Electron Microscope (SEM), Transmission Electron Microscope(TEM), Zeta potential and Zeta size analysis was done through data. It was determined that AgNPs have maximum absorbance at 443 nm wavelength, they exhibit 14.67 crystal nano size, -19.9 mV zeta potential in spherical appearance. The Minimum Inhibition Concentration (MIC) of the obtained AgNPs was determined by using microdilution method on the growth of pathogen strains.